11‐Aza‐artemisinin Derivatives Exhibit Anticancer Activities by Targeting the Fatty Acid Binding Protein 6 (FABP6)2. Issue 12 (24th October 2018) - Chen, Xin‐Ya; Yin, Yue; Xi, Jie; Yuan, Yi; Li, Yan; Li, Qing; Wang, Ren‐Xiao; Yao, Zhu‐Jun; Tang, Gong‐Li
Abstract: Artemisinin (Qinghaosu), a sesquiterpene lactone isolated from the Chinese medicinal herb Artemisia annua, is famous as the first‐line antimalarial drug, and reported to also possess anticancer properties. Though many studies have proceeded focusing on artemisinin and bioactive derivatives in clinic or laboratory, their cellular targets and mechanism of actions have still remained obscure. Here, two new 11‐aza‐artemisinin derivatives AAD1 and AAD2, which displayed cytotoxity against multiple cancer cell lines, were synthesized and applied as the probes for target identification and anticancer mechanism research. Using T7 phage display screen method, fatty acid binding protein 6 (FABP6) was identified and verified as one of the potential targets. Further studies showed FABP6 is a direct binding protein of AAD1 and AAD2, and mediated the corresponding anticancer activities of these artemisinin derivatives. Abstract : Two new anticancer 11‐aza‐artemisinin derivatives AAD1 and AAD2 with terminal amino groups were successfully synthesized, evaluated and applied as the probes for the study of target identification and mechanism of action. FABP6 potein was identified and further confirmed as one target of these azaartemisinin derivatives.